Clinically suspected acute recurrent pulmonary embolism: A diagnostic challenge - Nijkeuter, Mathilde; Kwakkel-van Erp, Hanneke; Söhne, Maaike; Tick, Lidwine W.; Kruip, Marieke J. H. A.; Ullmann, Eric F.; Kramer, Mark H. H.; Büller, Harry R.; Prins, Martin H.; Leebeek, Frank W. G.; Huisman, Menno V. (Thrombosis and Haemostasis, 2007)
It is unknown whether strategies validated for diagnosing pulmonary embolism (PE) are valid in patients with a history of PE. It was the objective of this study to investigate whether a diagnostic algorithm consisting of sequential application of a clinical decision rule (CDR), a quantitative D-dimer test and computed tomography (CT) safely ruled out a clinical suspicion of acute recurrent PE. Data were obtained from a diagnostic outcome study of patients suspected of PE. Acute recurrent PE was ruled out by an unlikely probability of PE (CDR score ≤4 points) combined with a normal D-dimer test (≤500 ng/ml) or by a normal CT in all other patients. The primary outcome was the incidence of acute recurrent venous thromboembolism during three months of follow-up in patients with normal tests and not treated with anticoagulants. Of 3,306 patients suspected of acute PE, 259 patients (7.8%) had a history of PE of whom 234 were not treated with anticoagulants. The probability of PE was unlikely in 82 of 234 patients (35%), and 42 had a normal D-dimer test (18%), excluding recurrent PE. None of these patients had a thrombotic event during follow-up (0%, 95%CI: 0–6.9). A CT was indicated in all other patients (192) and ruled out recurrent PE in 127 patients (54%). Only one patient with a negative CT had a fatal recurrent PE during follow-up (0.8%; 95%CI: 0.02–4.3). In conclusion, this prospective study demonstrates the safety of ruling out a clinical suspicion of acute recurrent PE by a simple diagnostic algorithm in patients with a history of PE.
Keywords: Recurrent pulmonary embolism; Diagnosis; computed tomography